Vitamin D levels and high-residual platelet reactivity in patients receiving dual antiplatelet therapy with clopidogrel or ticagrelor. (17th August 2016) - Verdoia, Monica; Pergolini, Patrizia; Rolla, Roberta; Sartori, Chiara; Nardin, Matteo; Schaffer, Alon; Barbieri, Lucia; Daffara, Veronica; Marino, Paolo; Bellomo, Giorgio; Suryapranata, Harry; De Luca, Giuseppe; et al.
Abstract: Background : Suboptimal platelet inhibition still represents an important challenge, especially for patients undergoing percutaneous coronary interventions (PCIs). However, very few are known so far on the predictors of high-residual platelet reactivity (HRPR) despite antiplatelet strategies. Increasing attention has been paid in the last years to the role of vitamin D in atherothrombosis. Therefore, the aim of our study was to evaluate the impact of vitamin D levels on platelet function in patients treated with dual antiplatelet therapy (DAPT). Patients treated with DAPT (ASA and clopidogrel or ticagrelor) after a recent acute coronary syndrome (ACS) or elective PCI were scheduled for platelet function assessment at 30–90 days post-discharge. Platelet function was assessed by whole blood impedance aggregometry (Multiplate®-Roche Diagnostics AG), HRPR was considered for ASPI test values > 862 AU*min (for ASA) and adenosine diphosphate (ADP) test values ≥417 AU*min (for ADP-antagonists). Fasting samples were obtained for main chemistry parameters and vitamin D level assessment. Our population is represented by 503 patients, who were divided according to vitamin D quartiles (≤9.1; 9.2–14.4; 14.5–21.7; >21.7 ng/ml). Lower vitamin D levels related with age ( p = 0.04), diabetic status ( p = 0.05), and previous coronary surgery ( p = 0.007), therapy with beta-blockers and statins ( p = 0.01 and p = 0.02). Vitamin D inversely related to the levels of total cholesterol ( p = 0.01), triglycerides ( p < 0.001), hemoglobin ( p = 0.05), and HbA1c ( p < 0.001). Significantly higher platelet reactivity was observed after platelet stimulation with ADP ( p = 0.01), but not with other platelet activators. The prevalence of HRPR for ASA was low (1.2%) and not conditioned by Vitamin D levels (adjusted OR[95%CI] = 1.56[0.71–3.5], p = 0.27). HRPR with ADP-antagonists was observed in 26% of patients, and the rate increased with lower vitamin D quartiles (37.3% vs 22.2% vs 24.4% vs 20.2%, p = 0.005, adjusted OR[95%CI] = 1.23[1.02–1.49], p = 0.04). An absolute increase in HRPR with lower vitamin D levels was similarly observed among patients receiving ticagrelor (adjusted OR[95% CI] = 1.40[0.95–2.06], p = 0.08), and those on clopidogrel (adjusted OR[95%CI] = 1.31[0.99–1.75], p = 0.06). Thus, lower vitamin D levels are associated with higher platelet reactivity and impaired effectiveness of ADP-antagonists, while not influencing the effectiveness of ASA. Future studies will tell whether vitamin D supplementation can reduce platelet reactivity, overcoming the phenomenon of resistance to antiplatelet agents.